A Genealogy Of Human Resource Management: Traditions, Transformations, Optimization Through Information Technology - Keikhosrokiani, Pantea; Asl, Moussa Pourya (Future Academy, 2017)
Advancement in technology and the ensuing rapid growth of Internet usage in recent decades, alongside with the evolution of organizational systems and software have driven organizations to replace traditional modes of Human Resource Management (HRM) with modern methods. The subsequent transformations, nonetheless, have engendered indispensable repercussions on the entirety of the organizations, affecting their whole configuration and structure, and unavoidably impacting on pivotal departments like human resource. Designing an organizational chart, for instance, that displayed human resources and the linkage among various sections and units became a prerequisite in setting up of any organization. The aim of the present study is threefold: First, it attempts to offer a genealogy of HRM transformation from traditional to modern pattern; then, it seeks to explicate the manner technological advancement has changed the direction of HRM; and finally, it aims at proposing a seven-goal-model for managers to optimize HRM process in future. The proposed model suggests that organizations must move up at a parallel way with the contemporary technological growth to be included and to survive in the existing competitive world. To achieve this final goal, the study also identifies the limitations of current HRM and in so doing attempts to offer novel directions for future studies.